Pengaruh Kemampuan Kerja Terhadap Kinerja Yang Dimediasi Oleh Motivasi Aparatur: Studi Pada Aparatur Kecamatan Proppo Kabupaten Pamekasan - Fatimah Riswati; Hadi Susanto; Sri Mulyani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Fatima, 2025. The Influence of Work Ability on Performance Mediated by Civil Servant Motivation . Postgraduate Program, Wijaya Putra University, Surabaya . Based on its approach, this research is included in the explanatory research type . The research sample was 71 respondents. The objectives of this research are 1) To test and analyze the significant influence of work ability on the performance of the apparatus of Proppo District , Pamekasan Regency . 2) To test and analyze the significant influence of work ability on the motivation of the apparatus of Proppo District ,Pamekasan Regency. 3) To test and analyze the significant influence of the motivation of the apparatus on the performance of the apparatus of Proppo District , Pamekasan Regency. 4) To test and analyze the significant indirect influence of work ability on the performance of the apparatus of Proppo District, Pamekasan Regency mediated by the motivation of the apparatus. The research results show that : 1) work ability has a significant positive effect on the performance of the apparatus of Proppo District , Pamekasan Regency with an original sample value of 0.284 . 2) work ability has a significant positive effect on the motivation of the Proppo District apparatus in Pamekasan Regency with an original sample value of 0.481. 3) the motivation of the apparatus has a significant positive effect on the performance of the apparatus of Proppo District, Pamekasan Regency with an original sample value of 0.658 . 4) work ability has a significant positive effect on the performance of the apparatus of Proppo District , Pamekasan Regency mediated by the motivation of the apparatus with an original sample value of 0.316.